The power of civil society in the Middle East and North Africa: peace-building, change, and development - Natil, Ibrahim; Pierobon, Chiara; Tauber, Lilian (Routledge explorations in development studies, 2019)
This book investigates the power of civil society in the Middle East and North Africa (MENA), in the context of the post-Arab Spring era, as well as more long-standing challenges and constraints in the region. In recent years, local civil society actors have faced significant challenges from social conservatism, conflict, violence, and the absence of democracy and exclusive political systems. Over the course of the book, the authors investigate how the sector has succeeded in achieving its own objectives despite these shifting conditions, the restrictive political environment and the complexity of the socio-cultural and economic context. Structured around the three themes of peace-building, development, and change, the book also addresses challenges faced by civil society organizations linked to ethnic, linguistic, and cultural diversities as well as religious salient differences that are crucial markers of social and political identity. Case studies are drawn from the Palestinian Occupied Territories, Jordan, Iran, Nigeria, Niger, Egypt, and Morocco, and particular effort has been made to showcase original research from contributors who are from the region .